Acid Drainage From Derelict Coal Mines in an Urban û Rural Environment of New South Wales ù Holding a Tiger by the Tail (The Australasian Institute of Mining and Metallurgy, 2003)
The New South Wales Department of Mineral Resources has, since 1974, administered the Derelict Mines Rehabilitation Program (DMRP) to reduce the environmental impacts of abandoned and orphan mine sites. The application of the DMRP is presented in case studies of sites from the South Maitland Coalfield featuring residual drainage of acidic and saline water in a semi urban and rural community setting. The acidity here is typically derived from iron oxidation in shallow underground coal mine workings and in surface emplacements of coal washery reject materials. This paper presents summary information on AMD investigation, monitoring and rehabilitation. The experiences of community expectation, stakeholder consultation and peer review are discussed.